2012
DOI: 10.5535/arm.2012.36.1.112
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Test Results and Standardized Method in Quiet Standing Balance Evaluation

Abstract: ObjectiveTo identify factors affecting test results of the quiet standing balance evaluation conducted by posturography and to investigate the standardized method by comparing results according to feet width.MethodThe study cohort consisted of 100 healthy individuals. We assessed the quiet standing balance of subjects by using 3 different methods: standing on a force plate with feet width the same as shoulder width (test 1); with feet width the same as half the shoulder width (test 2); with feet width determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
3
11
2
Order By: Relevance
“…Several other studies have demonstrated that visual deprivation and the imprecision of proprioceptive information increase center of pressure displacement (26,27,28). Nonetheless, we were not able to find studies in the literature showing vision deprivation, with or without imprecision of proprioceptive information, to cause more negative impact on men than on women.…”
Section: Limitations Of the Studycontrasting
confidence: 77%
“…Several other studies have demonstrated that visual deprivation and the imprecision of proprioceptive information increase center of pressure displacement (26,27,28). Nonetheless, we were not able to find studies in the literature showing vision deprivation, with or without imprecision of proprioceptive information, to cause more negative impact on men than on women.…”
Section: Limitations Of the Studycontrasting
confidence: 77%
“…The Non-significant results for height and its proportion of this study contradicts the previous literature [8,[10][11][12] which supports the influence of height on balance by virtue of higher placement of COG in relation to BOS in taller individuals. Results of this study are consistent with the Jung Joong Yoon, et al [38] that revealed the no relationship between height and balance sway. There are studies [10,11] that affirm the influence of height and either of its proportion on medio-lateral sway in quite standing instead of antero-posterior directional sway.…”
Section: Discussionsupporting
confidence: 82%
“…Multiple robust regression with Huber's method was used for the other variables due to heteroskedasticity [27]. We adjusted for age and gender (model 1) in all analyses because age has been shown to influence several of the variables measured [28][29][30] and gender was not equally distributed between the groups (Table 1). In the analyses of CM we also adjusted for maximum ROM in the primary plane (model 2) and in the final model for both maximum ROM and peak velocity in the primary plane ROM test (model 3), since these covariates are shown to influence smoothness of movement in previous studies [31].…”
Section: Discussionmentioning
confidence: 99%